Air-Liquid Interface: Relevant In Vitro Models for Investigating Air Pollutant-Induced Pulmonary Toxicity. (9th March 2018) - Upadhyay, Swapna; Palmberg, Lena
Abstract: Air pollution leads to inhalation of several pulmonary stimulants that includes particulate matter, and gaseous substances contributing significantly to the development of chronic lung diseases. However, the pathophysiological mechanism of air pollutant mediated pulmonary toxicity remains unclear. This is primarily due to the lack of efficient test systems, mimicing human inhalation exposure scenarios to air pollutants. The majority of the pulmonary in vitro studies have been conducted using cell lines in submerged cell culture conditions and thereby overlooking the pulmonary physiology. Moreover, submerged cell culture systems lack the possibility to measure effective dose measurements. Particle properties, such as size, surface charge, solubility, transformation, or agglomeration state and chemical properties are altered in solution and are dependent on the composition of cell culture medium. Physiologically relevant in vivo -like in vitro models cultured at air-liquid interface (ALI) is therefore becoming a realistic and efficient tool for lung toxicity testing and cell-cell interaction studies following exposure to aerosolized or gaseous form of air pollutants. Primary bronchial epithelial cells cultured at ALI leads to differentiate into respiratory epithelium consisting of ciliated cells, goblet cells, club cells and basal cells. ALI system is also considered as a feasible approach to implement the "3R principle"—replacement, reduction, and refinement of animal usage in lung toxicity studies. This review discusses the current understanding of relevance, benefits and limitations of the ALI models in comparison to the existing in vitro and in vivo exposure system for testing air pollutants mediated pulmonary toxicity.